2002
DOI: 10.1007/s11325-002-0045-9
|View full text |Cite
|
Sign up to set email alerts
|

Association of Sleep and Academic Performance

Abstract: Poor school performance by adolescent students has been attributed in part to insufficient sleep. It is recognized that a number of factors lead to diminished total sleep time and chief among these are early school start times and sleep phase delay in adolescence. Political initiatives are gaining momentum across the United States to require later school start times with the intent of increasing total sleep time and consequently improving school performance. Later school start times come with significant costs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
39
0
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 20 publications
3
39
0
4
Order By: Relevance
“…For example, sleep disturbances at 16 years of age predict sleep disturbances in adulthood (Dregan & Armstrong, 2010). However, although the relationship between sleep length and academic performance has been meta-analyzed (Dewald et al, 2010), some studies have not found associations between sleep quantity or quality and academic achievement (Eliasson et al, 2002).…”
Section: Sleep and Academic Performancementioning
confidence: 99%
“…For example, sleep disturbances at 16 years of age predict sleep disturbances in adulthood (Dregan & Armstrong, 2010). However, although the relationship between sleep length and academic performance has been meta-analyzed (Dewald et al, 2010), some studies have not found associations between sleep quantity or quality and academic achievement (Eliasson et al, 2002).…”
Section: Sleep and Academic Performancementioning
confidence: 99%
“…Our search strategy resulted in 18 studies in total, including 10 cross-sectional studies comparing 2 contemporaneous student populations with different start times, 18,19,23,24,26,[28][29][30][31][32] 7 prospective studies evaluating the effect of school start times within the same school populations, 8,17,20,21,[33][34][35] and 1 retrospective historical cohort study that compared outcomes in school populations of one geographical area separated by many years (and therefore different actual students). 36 Although most studies evaluated public school populations, two prospective studies evaluated the effect of school-start time changes on outcomes in a boarding school population.…”
Section: Evidence Basementioning
confidence: 99%
“…1 However, others have found no signifi cant association between academic performances and sleep duration in adolescents or in medical college students. 2,3 This discrepancy may be explained by the fact that sleep duration cannot exactly represent the unmet sleep need for each individual.…”
mentioning
confidence: 99%